First-Year Students’ Perspectives on the Use of Digital Flashcards in Learning French Reading Skills at the A1 Level - Wiwid Nofa Suciaty; Aprilia (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to identify the perspectives of first-year students in the French Language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Jakarta, regarding the use of digital flashcards in learning French reading skills at the A1 level. The research was conducted in the French Language Education Study Program of the Faculty of Languages and Arts at Universitas Negeri Jakarta in 2025. The population of this study consisted of first-year students enrolled in the reading skills course (réception écrite), with a total sample of 62 students. The research instrument was a 20-item Likert-scale questionnaire to measure students’ perceptions, needs, and experiences regarding the use of learning media in reading activities. The data were analysed using a quantitative descriptive method, and the percentage of students’ responses to each statement was calculated. The results show that 95% of students are aware that reading skills are an essential competence in learning French. However, 71% of students reported difficulties understanding French texts, particularly with new vocabulary, sentence structure, and overall comprehension. In addition, 89% of students stated that they need support for learning media to facilitate the reading process, and 87% reported feeling more helped when the material is presented through visual media.““Furthermore, 92% of students indicated that digital flashcards are needed for French language learning. Although the use of digital flashcards is still relatively rare in classroom practice, students demonstrate very positive perceptions of this medium. Therefore, the development of digital flashcards can be considered a relevant and potential solution to support the learning of reading skills for beginner-level French learners (A1).